2017
DOI: 10.1200/jco.2017.35.15_suppl.e17521
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment 18F-FDG PET-CT for nasopharyngeal carcinoma patients.

Abstract: Background: Nasopharyngeal carcinoma (NPC) is a special subtype of head and neck cancer (HNC). At present, there are no highly specific prognostic markers to aid in tumor grading and guide patient treatment modalities for NPC. The prognostic value of pretreatment 18 F-fluorodeoxyglucose positron emission tomography-computed tomography ( 18 F-PET-CT) in NPC patients is controversial and no consensus exists as to its predictive capability.Methods: To analyze the predictive efficacy of 18 F-PET-CT imaging in NPC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The standard uptake value (SUV) is the parameter used to evaluate the degree of FDG uptake in PET / CT. Tumor SUV value is thought to be related with tumor aggressiveness and prognosis [34]. Previous studies on colon cancer, non-small cell lung cancer and nasopharyngeal cancer have shown that tumor SUV max value is associated with prognosis and higher SUV max value is associated with poorer survival [34][35][36]. In our study, PFS was found to be better in patients with high tumor SUV max value in the survival analysis performed in all patients and the group receiving bevacizumab therapy.…”
Section: Discussionsupporting
confidence: 51%
“…The standard uptake value (SUV) is the parameter used to evaluate the degree of FDG uptake in PET / CT. Tumor SUV value is thought to be related with tumor aggressiveness and prognosis [34]. Previous studies on colon cancer, non-small cell lung cancer and nasopharyngeal cancer have shown that tumor SUV max value is associated with prognosis and higher SUV max value is associated with poorer survival [34][35][36]. In our study, PFS was found to be better in patients with high tumor SUV max value in the survival analysis performed in all patients and the group receiving bevacizumab therapy.…”
Section: Discussionsupporting
confidence: 51%
“…6 Recently, many other kinds of prognostic factors have been found for NPC, including Epstein-Barr virus oncogene subvariant; leucinerich repeats and immunoglobulin-like domains gene status and its mRNA and protein expression levels; the maximum standard uptake value, metabolic tumor volume, and total lesion glycolysis of positron emission tomography/computed tomography; and tumor diameter. [7][8][9][10][11] However, the majority of these factors are not suitable for clinical practice for various reasons, such as having a high cost or low specificity. A more accurate appraisal system is urgently needed.…”
mentioning
confidence: 99%
“…The optimal cut-off value of metastatic lymph nodes size as N3 criteria needs to assess using a more reliable algorithm. Third, the tumor volume [13,14] and metabolic tumor volume [15][16][17][18] may be better factors than the metastatic lymph nodes size in representing the tumor burden. These factors might replace the maximal lymph nodal diameter in further staging systems.…”
Section: Discussionmentioning
confidence: 99%